The Impact of Arabic Dialects on The Content and Stylistic Features of Literary Texts: A Historical ond Contemporary Analysis - Bakhromkhodja, Makhamadkhodjaev (Pubmedia Social Sciences and Humanities, 2025)
This article examines the impact of Arabic dialects on the content and stylistic features of literary texts. It analyzes the historical roots of dialects, their connections with local cultures, and their significance in contemporary literature from linguistic and literary perspectives. The study provides examples of dialectal characteristics, their integration with poetic and prose works, and the objectives of writers in employing these features. The research opens new directions in the fields of linguistics and literary studies.